2014
DOI: 10.1159/000358174
|View full text |Cite
|
Sign up to set email alerts
|

The Increasing Prevalence of Multiple Sclerosis in New Zealand

Abstract: Background: New Zealand (NZ) has a high prevalence of multiple sclerosis (MS). Worldwide, the prevalence of MS appears to be increasing. Objectives: To review all published prevalence studies undertaken in NZ to determine whether the prevalence of MS in NZ is increasing. Methods: PubMed, Medline, Scopus, Web of Knowledge, EMBASE, AMED and CINAHL were searched to identify studies reporting the prevalence of MS in NZ. Prevalence rates from the National MS Prevalence study in 2006 were compared with earlier preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“… 31 In New Zealand, studies performed between 1968 and 2001 consistently reported a female-to-male ratio of 2.5:1 to 3:1. 32 In all, even the higher end of the increased female-to-male ratio range reported recently, is lower than the ratio in the MSmonitor population. So, it seems that female PwMS were either preferentially invited to participate or were more prone to use MSmonitor.…”
Section: Discussionmentioning
confidence: 62%
“… 31 In New Zealand, studies performed between 1968 and 2001 consistently reported a female-to-male ratio of 2.5:1 to 3:1. 32 In all, even the higher end of the increased female-to-male ratio range reported recently, is lower than the ratio in the MSmonitor population. So, it seems that female PwMS were either preferentially invited to participate or were more prone to use MSmonitor.…”
Section: Discussionmentioning
confidence: 62%
“… 16 In terms of absolute number of people affected by neurological disorders, most of the increase in the burden was associated with ageing of the population and population growth. 9 Increasing incidence of stroke in low-income and middle-income countries, 17 increasing prevalence of multiple sclerosis, 18 , 19 increasing incidence of epilepsy in elderly people, 20 increasing prevalence of tension-type headache, 21 and increasing incidence of brain tumours in elderly people 22 have been reported elsewhere. Findings from other studies have reported that it is difficult to assess trends in prevalence and incidence of Parkinson's disease because of changes in case definitions over time.…”
Section: Discussionmentioning
confidence: 99%
“…There was a large rise in the absolute numbers of prevalent cases of Alzheimer's disease and other dementias ( 44 , 45 ). In addition, an increasing incidence of stroke ( 46 ), epilepsy ( 47 ), and intracranial malignancies in elderly people ( 48 ), as well as growing prevalence of multiple sclerosis ( 49 , 50 ) have been reported in different regions. The increasing burden of these neurological conditions, found to be an established risk factor for BP, may account for part of the rising incidence of BP.…”
Section: Putative Explanations For This Surgementioning
confidence: 99%